Aspectos fisioecológicos de Astyanax fasciatus e Pimelodus maculatus (teleósteos) do reservatório da UHE de Furnas, MG: avaliação morfofuncional das brânquias e variáveis hematológicas - Henrique, Helen Sadauskas (Universidade Federal de São Carlos, 2008)
The aim of this study was to evaluate the morphofunctional structure of the gills and the hematological variables of Astyanax fasciatus and Pimelodus maculatus living on Furnas Dam Reservoir (Minas Gerais State, Brazil) and analyses the influence of water quality on these parameters. The fishes were collected in five sites (FU10: Turvo; FU20: Guapé; FU30: Barranco Alto; FU40: Fama and FU50: Porto Fernandes) during June and December/2006. Physico-chemical variables and organochlorides content of the water and heavy metals on the sediment were performed. Gills and blood samples were taken for check inquire of the composition of the water on the presence of histopathologys and differentiation of chloride and mucous cells and differences on the hematological variables of the fishes collected on the different sites. Hyperplasia and hypertrophy of the respiratory epithelium, lamellar fusion, epithelial lifting, oedema and chloride cells proliferation were the most common histopathological damages observed on the gills for both species. The histopathological alteration index of the gills indicates some degree of lesions that engage the normal function of the organ in A. fasciatus collected in June. Heavy metals, as copper seems to promote alterations on the red blood cells for both fishes during the sampling. While, some pollutants as endosulfan, metolachloride, copper and chromium seems to causes a stimulation of the immune system of the fishes; this effect was most common on the fishes collected in the sites: FU10, FU20 and FU30. The condition factor (K and Kn) of the fishes has been affected by the presence of chromium on the sediment, especially in the site FU30 during the two months. Over all, these results indicates that the water quality in June and December (2006) of Furnas Dam reservoir could promote physiological and morphological alterations on the gills fishes to maintain the homeostase.
Ecophysiological aspects of Astyanax fasciatus and Pimelodus maculatus from Furnas dam (MG): morpho-functional evaluation of the gills and hematological variables
Keywords: Bioindicadores; Poluição; Teleósteos; Usina Hidrelétrica de Furnas, Reservatório da (MG); Variáveis hematológicas; Organoclorados; Histopatologia branquial; Teleostes; Furnas Dam; Hematological variables; Gills histopathology; Organochlorides; Heavy metals; CIENCIAS BIOLOGICAS::ECOLOGIA